2010
DOI: 10.3390/polym2040681
|View full text |Cite
|
Sign up to set email alerts
|

Glucan Particle Encapsulated Rifampicin for Targeted Delivery to Macrophages

Abstract: Glucan particles (GPs) are 2-4 m spherical, hollow, porous shells extracted from Baker's yeast, Saccharomyces cerevisae. The surface of the GPs is composed primarily of 1,3--glucan and the particles are efficiently phagocytosed via receptor-mediated cell uptake by macrophages, phagocytic cells expressing glucan receptors. The hollow cavity of the GPs allows for efficient absorption and encapsulation of payload molecules. Rifampicin (Rif), a drug used in tuberculosis treatment, was encapsulated by precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 21 publications
2
56
1
Order By: Relevance
“…These particles are easily phagocytized via receptor-mediated cell uptake by macrophages, wherein phagocytic cells communicate with glucan receptors. 44 The use of GPs for delivery of macromolecules, such as DNA, siRNA, and proteins, has been successfully established both in vitro and in vivo. 45,46 Soto et al have successfully encapsulated the TB antibiotic rifampin in glucan particles by making use of an alginate or chitosan hydrogel to close the GP pores and prolong the drug release.…”
Section: Inhalable Microparticles Of Polylactic Acidmentioning
confidence: 99%
See 4 more Smart Citations
“…These particles are easily phagocytized via receptor-mediated cell uptake by macrophages, wherein phagocytic cells communicate with glucan receptors. 44 The use of GPs for delivery of macromolecules, such as DNA, siRNA, and proteins, has been successfully established both in vitro and in vivo. 45,46 Soto et al have successfully encapsulated the TB antibiotic rifampin in glucan particles by making use of an alginate or chitosan hydrogel to close the GP pores and prolong the drug release.…”
Section: Inhalable Microparticles Of Polylactic Acidmentioning
confidence: 99%
“…45,46 Soto et al have successfully encapsulated the TB antibiotic rifampin in glucan particles by making use of an alginate or chitosan hydrogel to close the GP pores and prolong the drug release. 44 The void holes of the GPs permit the efficient absorption and encapsulation of drugs. They have reported the sustained release for periods of 24-72 hours in vitro and have found that the formulation diminishes the intracellular TB count in infected bone marrow-derived macrophages.…”
Section: Inhalable Microparticles Of Polylactic Acidmentioning
confidence: 99%
See 3 more Smart Citations